Assessing supraglacial lake depth using ICESat-2, Sentinel-2, TanDEM-X, and in situ sonar measurements over Northeast and Southwest Greenland - Lutz, Katrina; Bever, Lily; Sommer, Christian; Seehaus, Thorsten; Humbert, Angelika; Scheinert, Mirko; Braun, Matthias (Cryosphere, 2024)
Supraglacial lake development in Greenland consists of intricate hydrological processes, contributing not only to surface mass loss but also to a lowering of the surface albedo and changes in ice dynamics. While the estimation of lake area has recently improved, the determination of the lake volume is essential to properly estimate the amount of water contained in and lost from supraglacial lakes throughout the melt seasons. In this study, four supraglacial lake depth estimation methods, including two new empirical approaches, are presented and compared. The empirical methods were developed to relate Sentinel-2 reflectance values to supraglacial lake depth obtained from (1) ICESat-2 (Ice, Cloud and land Elevation Satellite 2) crossings over 19 lakes in Northeast and Southwest Greenland and (2) in situ sonar tracks from four lakes on Zachariae Isstrom (Zachariæ Isstrøm) in Northeast Greenland. The depths from both equations were independently correlated to their corresponding Sentinel-2 reflectance values to create empirical relations. The third method is a standardly used radiative transfer model also based on Sentinel-2 data. Finally, the depths for five lakes in Northeast Greenland were derived from TanDEM-X (TerraSAR-X add-on for Digital Elevation Measurement) digital elevation models after lake drainage. All four methods were applied to the five lakes for which digital elevation models were procured, allowing for a direct comparison of the methods. In general, the sonar-based empirical equation aligned best with the estimates from the digital elevation model until its saturation point of 8.6 m. Through the evaluation of the ICESat-2-based equation, a strong influence of lake bed sediment on depth estimation could be seen. The ICESat-2 empirically derived depth equation produced slightly deeper depths than the sonar-based equation. The radiative transfer model more strongly overestimated nearly all depths below its saturation point of 16.3 m, when compared to the digital elevation model results. This large overestimation can be primarily attributed to the sensitivity of this method’s parameters. Furthermore, all methods, with the exception of the digital elevation model, were applied to an area in Northeast Greenland on the peak melt dates for the years 2016–2022 to explore lake volume interannual variability. Finally, a closer examination of the uncertainties for each method provides insight into associated errors and limitations when considering which method to use for supraglacial lake depth estimation. Overall, empirically derived equations are shown to be capable of simplifying supraglacial lake depth calculations while also retaining sufficient accuracy under low-sediment, floating-ice-free, and atmospherically clear conditions.
CRIS-Team Scopus Importer:2024-12-13